Regulation of Chromatin Structure During Neural Development - Kishi, Yusuke; Gotoh, Yukiko (Frontiers in Neuroscience, 2018)
The regulation of genome architecture is a key determinant of gene transcription patterns and neural development. Advances in methodologies based on chromatin conformation capture (3C) have shed light on the genome-wide organization of chromatin in developmental processes. Here we review recent discoveries regarding the regulation of three-dimensional chromatin conformation, including promoter-enhancer looping and the dynamics of large chromatin domains such as topologically associated domains (TADs) and A/B compartments. We conclude with perspectives on how these conformational changes govern neural development and may go awry in disease states.